In Situ Assessment of Porcine Osteochondral Repair Tissue in the Visible–Near Infrared Spectral Region - Kandel, Shital; Querido, William; Falcon, Jessica M.; Zlotnick, Hannah M.; Locke, Ryan C.; Stoeckl, Brendan; Patel, Jay M.; Patil, Chetan A.; Mauck, Robert L.; Pleshko, Nancy (Frontiers in Bioengineering and Biotechnology, 2022)
Standard assessment of cartilage repair progression by visual arthroscopy can be subjective and may result in suboptimal evaluation. Visible-near infrared (Vis-NIR) fiber optic spectroscopy of joint tissues, including articular cartilage and subchondral bone, may provide an objective approach for quantitative assessment of tissue composition. Here, we applied this technique in the 350-2500 nm spectral region to identify spectral markers of osteochondral tissue during repair with the overarching goal of developing a new approach to monitor repair of cartilage defects in vivo. Full thickness chondral defects were created in Yucatan mini pigs using a 5 mm biopsy punch and microfracture (MFx) was performed as a standard technique to facilitate repair. Tissues were evaluated at 1 and 3-months post-surgery by spectroscopy and histology. After euthanasia, Vis-NIR spectra were collected in situ from the defect region. Additional spectroscopy experiments were carried out in vitro to aid in spectral interpretation. Osteochondral tissues were dissected from the joint and evaluated using the conventional International Cartilage Repair Society (ICRS) II histological scoring system, which showed lower scores for the 1 month compared to the 3 month repair tissues. In the visible spectral region, hemoglobin absorbances at 540 and 570 nm were significantly higher in spectra from 1 month repair tissue compared to 3 months repair tissue, indicating a reduction of blood in the more mature repair tissue. In the NIR region, we observed qualitative differences between the two groups in spectra taken from the defect, but differences did not reach significance. Further, spectral data also indicated that the hydrated environment of the joint tissue may interfere with evaluation of tissue water absorbances in the NIR region. Together, these data provide support for further investigation of the visible spectral region for assessment of longitudinal repair of cartilage defects, which would enable assessment during routine arthroscopy, in particular in a hydrated environment.